Is Environmental Governance Substantive or Symbolic? An Empirical Investigation - Rodrigue, Michelle (Journal of business ethics, 2013)
The emergence of environmental governance practices raises a fundamental question as to whether they are substantive or symbolic. Toward that end, we analyze the relationship between a firm’s environmental governance and its environmental management as reflected in its ultimate outcome, environmental performance. We posit that substantive practices would bring changes in organizations, most notably in terms of improved environmental performance, whereas symbolic practices would portray organizations as environmentally committed without making meaningful changes to their operations. Focusing on a sample of environmentally sensitive firms, results are consistent with environmental governance mechanisms being predominantly part of a symbolic approach to manage stakeholder perceptions on environmental management, having little substantial impact on organizations. Statistical analyses show mostly that there is no relation between environmental governance mechanisms and environmental performance, measured in terms of regulatory compliance, pollution prevention, and environmental capital expenditures. However, there is some indication that environmental incentives are associated with pollution prevention. Interviews with corporate directors shed further light on these results by underlining that environmental governance mechanisms are employed at the board level to protect the organization from reputational and/or regulatory harm, but are not necessarily intended to proactively improve environmental performance.